Alquran dan Kepemimpinan Non Muslim di Indonesia - Wildan Hidayat (JOURNAL OF QUR'AN AND HADITH STUDIES, 2018)
This paper discusses non-Muslim leadership in the context of modern Indonesia. By using descriptive analytic methods, the writer discusses verses about leadership and links them to the pros and cons about non-Muslim leadership. This study find that some Muslim scholars misused these verses to discredit non-Muslim leadership.